2016
DOI: 10.1242/jeb.132480
|View full text |Cite
|
Sign up to set email alerts
|

Wake analysis of aerodynamic components for the glide envelope of a jackdaw (Corvusmonedula)

Abstract: Gliding flight is a relatively inexpensive mode of flight used by many larger bird species, where potential energy is used to cover the cost of aerodynamic drag. Birds have great flexibility in their flight configuration, allowing them to control their flight speed and glide angle. However, relatively little is known about how this flexibility affects aerodynamic drag. We measured the wake of a jackdaw (Corvus monedula) gliding in a wind tunnel, and computed the components of aerodynamic drag from the wake. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 39 publications
2
34
0
Order By: Relevance
“…close to the one obtained by the subtraction method. By using PIV, Klein Heerenbrink et al () obtained values of C D,pro for a jackdaw of the same magnitude as the previous studies, with a minimum of 0.019. Hence, a value around 0.02 seems motivated on the basis of relatively large birds in gliding flight.…”
Section: Aerodynamic Equations Of Bird Flightsupporting
confidence: 61%
See 1 more Smart Citation
“…close to the one obtained by the subtraction method. By using PIV, Klein Heerenbrink et al () obtained values of C D,pro for a jackdaw of the same magnitude as the previous studies, with a minimum of 0.019. Hence, a value around 0.02 seems motivated on the basis of relatively large birds in gliding flight.…”
Section: Aerodynamic Equations Of Bird Flightsupporting
confidence: 61%
“…From time‐lapse images the vortex wake can be imaged and quantitative details derived, such as vorticity, circulation and body drag from the retardation of the airflow caused by the body. By using PIV, C D,par has been estimated for a common swift Apus apus at 0.25 (Henningsson and Hedenström ) and a jackdaw Corvus monedula in gliding flight at 0.20 (Klein Heerenbrink et al ), which are both higher than the 0.1 obtained from the in‐direct wing beat frequency method (Pennycuick et al ).…”
Section: Aerodynamic Equations Of Bird Flightmentioning
confidence: 95%
“…1; Movie 1). Application of automated Lagrangian particle tracking velocimetry (see Movie 2) to the study of bird flight is novel, though seeding the air with helium bubbles builds upon the early studies of animal flight (Spedding et al, 1984;Spedding, 1987); and wakes have been measured using smoke and particle image velocimetry for a range of considerably smaller flapping (Spedding et al, 2003;Warrick et al, 2005;Van Griethuijsen et al, 2006;Tobalske et al, 2009;Altshuler et al, 2009;Johansson et al, 2018) and gliding (Henningsson and Hedenström, 2011;Henningsson et al, 2014;KleinHeerenbrink et al, 2016) birds.…”
Section: Introductionmentioning
confidence: 99%
“…It may be that the selective pressures acting on wing tip morphology are more nuanced, complex, and species‐specific than what aerodynamic theory alone suggests. Previous research by Tucker () showed that emarginate primary feathers reduced drag in a gliding Harris's hawk, but more recent work contradicts these findings: A study exploring the wake behind a gliding jackdaw ( Corvus monedula ) showed that vertically separated primary feathers did not significantly affect efficiency (KleinHeerenbrink, Warfvinge, & Hedenström, ). A recent study of swept and extended wings with emarginate feathers showed that lift and drag coefficients (aerodynamic force per unit wing area) were virtually the same during emulated gliding flight, but varied significantly in emulated flapping flight and were predominantly mediated by changes in lift (Klaassen van Oorschot et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…It may be that the selective pressures acting on wing tip morphology are more nuanced, complex, and species-specific than what aerodynamic theory alone suggests. Previous research by Tucker (1993Tucker ( , 1995 showed that emarginate primary feathers reduced drag in a gliding Harris's hawk, but more recent work contradicts these findings: A study exploring the wake behind a gliding jackdaw (Corvus monedula) showed that vertically separated primary feathers did not significantly affect efficiency (KleinHeerenbrink, Warfvinge, & Hedenstr€ om, 2016).…”
mentioning
confidence: 97%